2004
DOI: 10.1002/qua.20054
|View full text |Cite
|
Sign up to set email alerts
|

Computing enthalpy–entropy interplay for isomeric fullerenes

Abstract: ABSTRACT:Fullerenes represent unique species in many respects, one of them being one of the highest temperature regions ever used for preparation of chemical species. This very factor automatically substantially enhances the importance of the TS part of the Gibbs function. The essential feature of fullerenic systems has consistently been ignored in computational studies of fullerenes, almost always drawing their conclusions from potential energies or heats of formation. This report demonstrates that the simpli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…He selected cage hydrocarbons (he called polyhedrans) based on Platonic or Archimedean polyhedra, including C 60 H 60 (fully hydrogenated fullerene C 60 ). His 50‐year‐old predictions, based only on very simple molecular mechanics, agree reasonably well with advanced present‐day calculations . They both point out the well‐known synthetic hydrocarbon dodecahedrane C 20 H 20 as the most stable cage hydrocarbon and C 60 H 60 as the third‐most stable (which comes before another synthetic polyhedrane, cubane C 8 H 8 ).…”
Section: The M06‐2x/6‐31++g** Encapsulation Energies δEenc For Water supporting
confidence: 60%
“…He selected cage hydrocarbons (he called polyhedrans) based on Platonic or Archimedean polyhedra, including C 60 H 60 (fully hydrogenated fullerene C 60 ). His 50‐year‐old predictions, based only on very simple molecular mechanics, agree reasonably well with advanced present‐day calculations . They both point out the well‐known synthetic hydrocarbon dodecahedrane C 20 H 20 as the most stable cage hydrocarbon and C 60 H 60 as the third‐most stable (which comes before another synthetic polyhedrane, cubane C 8 H 8 ).…”
Section: The M06‐2x/6‐31++g** Encapsulation Energies δEenc For Water supporting
confidence: 60%
“…Using the same formula as that used by Slanina et al, 30 we calculated the relative concentration of the isomers without considering all the quantum effects to understand the classical results ͑Fig. 9͒, showing that the number of the D 6h cages should be about only 3% of the D 2d cages and formation of the other isomers would be ignored at all in the temperature range of about 2300 K ͑Fig.…”
Section: ͑1͒mentioning
confidence: 99%
“…[16,17] Experimentally, Kikuchi, Achiba and co-workers briefly reported that they had isolated ten isomers of C 96 and identified their symmetries through 13 C NMR spectroscopy as C 1 (4 isomers), C 2 (3 isomers), C s (l isomer), D 2 (1 isomer), and D 3d (l isomer). [18] Kemnitz and Troyanov reacted C 2 F 5 I with a mixture of higher fullerenes and were able to obtain crystals of the adduct C 96 A C H T U N G T R E N N U N G (C 2 F 5 ) 12 , which were shown by singlecrystal X-ray diffraction to utilize the C 1 A C H T U N G T R E N N U N G (145)-C 96 cage.…”
mentioning
confidence: 99%